Inspecting mother-to-infant microbiota transmission: disturbance of strain inheritance by cesarian section - Yang, Ru; Wang, Yinan; Ying, Zhiye; Shi, Zeyao; Song, Yan; Yan, Jing; Hou, Shulin; Zhao, Zicheng; Hu, Yanling; Chen, Qiong; Peng, Wentao; Li, Xiaowen (Frontiers in Microbiology, 2024)
The initial acquisition and subsequent development of the microbiota in early life is crucial to future health. Cesarean-section (CS) birth is considered to affect early microbial transmission from mother to infant. In this studyHere, we collected fecal samples from 34 CS infants and their mothers from West China Second Hospital, Sichuan University to assceess the microbiota developmental trajectory of mothers and infants., Weand explored mother-infant gut microbiome transmission via comparisonng with corresponding a Finnish data. Metagenomic analysis of gut microbiota profiles indicated that the communities of mothers and infants were clearly distinct. The composition of the infant gut microbiome wasis highly variable but also followed s predictable patterns in the early stages of life. Maternal communities were stable and mainly dominated by species from Bacteroidacea spp. Then, wWe used PStrain to analyze and visualize strain transmission in each mother-infant pair. Excluding missing data (2), we included 32 mother-infant pairs for analysis of strain transmission. Most CS deliveries (65.6%, 21/32) did not demonstrate transmission of strains from mother to infant. To further explore the mother-infant strain transmission, we analyzed a metagenomics data from Finnish mother-infant pairs. A total of 32 mother-infant pairs were included in the analysis, including 28 vaginal delivery (VD) infants and four CS infants. Strain transmission was observed in 30 infants, including 28 VD infants and two2 CS infants. All the VD infants received transmitted stains from their mothers.Finally, a total of 193 strains transmission events were observed, including comprising 131 strains and 45 species. Taken tTogether, our data suggested that delivery mode was an the most important factor influencing the mother-infant strain transmission.